2017
DOI: 10.1007/s40271-017-0267-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the European Health Literacy Survey Questionnaire in Patients with Stroke: A Latent Trait Analysis Using Rasch Modeling

Abstract: We recommend using the 12-domain scores of the rescaled HLS-EU-Q to comprehensively and accurately capture the competencies to access, understand, appraise, and apply health information within the three health contexts of healthcare, disease prevention, and health promotion for patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…The European Health Literacy Survey Questionnaire (HLS-EU-Q47) was developed on the basis of this framework [2,38,39]. However, Finbråten et al [40] and Huang et al [41] have revealed several psychometric weaknesses of the HLS-EU-Q47 when validated in people with T2DM and in people with stroke, respectively. The newly developed and shortened version of this instrument, the HLS-Q12, which has enhanced psychometric properties [42,43], was well-suited for HL screenings in the study sample of people with T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Health Literacy Survey Questionnaire (HLS-EU-Q47) was developed on the basis of this framework [2,38,39]. However, Finbråten et al [40] and Huang et al [41] have revealed several psychometric weaknesses of the HLS-EU-Q47 when validated in people with T2DM and in people with stroke, respectively. The newly developed and shortened version of this instrument, the HLS-Q12, which has enhanced psychometric properties [42,43], was well-suited for HL screenings in the study sample of people with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy across levels of person factors, general health, diabetes outcome, health behaviours and empowerment HL: person-location estimates (logit values) of health literacy by means of the HLS-Q12 of Finbråten et al[41]. Higher values indicate higher HL…”
mentioning
confidence: 99%
“…The survey was initiated by the Action Network on applied in a population study in eight European countries in 2011 [1] and in Norway in 2014-2015 [6,7]. An accumulated body of corroborating evidence showed that the HLS-EU-Q47 data is not unidimensional [6][7][8][9][10][11], which gave rise to a controversy that led to the publication of the HLS-Q12 short form [7]. Subsequent to its publication, there has been an international request to establish the HLS-Q12 cutoff scores for different HL levels.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the advantages that item response theory (IRT) models, and Rasch models in particular, have over classical test theory (CTT), few health-related and health literacy scales have been evaluated using IRT and Rasch models (see, for example, Davidson, Keating & Eyres, 2004;Escobar et al, 2015;Huang et al 2018;Nguyen, Paasche-Orlow, Kim, Han and Chan, 2015). One such advantage is concerned with the assumption of item-sample independence, which is strongly emphasized in IRT and Rasch models.…”
Section: Introductionmentioning
confidence: 99%